Stress distribution in implant-supported prostheses using different connection systems and cantilever lengths: Digital photoelasticity - Goiato, Marcelo Coelho [UNESP] (2016)
Photoelastic analysis was used to evaluate the biomechanical behaviour of implant-supported, double-screwed crowns with different connection systems and cantilever lengths. Three models were made in PL-2 photoelastic resin and divided into six groups, on the basis of the implant connection system (external hexagon [EH] or Morse taper [MT]), type of abutment (Mini Pilar [Neodent, Curitiba, Paraná, Brazil] or UCLA) and number of crowns in the cantilever (one or two). The implant-prosthesis unit was placed in a circular polariscope. Occlusal surfaces of the crowns were subjected to 100-N loads in the axial and oblique (45°) directions in a universal testing machine (EMIC). Generated stresses were recorded and analysed qualitatively in a graphics program (Adobe Photoshop). Under axial loading, all of the groups had similar numbers of fringes, which were increased when the crowns were subjected to oblique loading. The highest number of fringes was found during oblique loading in the EH + Mini Pilar group. In conclusion, although the type of implant connection system did not have a direct influence on the stress distribution for axial loading, the cantilever length did have a direct influence on stress distribution. Models with two crowns in the cantilever showed more stress, with a greater concentration of force on the cervical part of the implant.